The effectiveness of a complaint-based ethics enforcement system: Evidence from the accounting profession - Beets, S. Douglas (Journal of business ethics, 1990)
Many professions, in order to enforce their ethics codes, rely on a complaint-based system, whereby persons who observe or discover ethics violations may file a complaint with an authoritative body. The authors assume that this type of system may encourage ethical behavior when practitioners believe that a punishment is likely to result from a failure to adhere to the rules. This perceived likelihood of punishment has three components: detection risk, reporting risk, and sanction risk. A survey of potential violation witnesses related to the accounting profession revealed that the profession's complaint-based enforcement system may not provide practitioners with the necessary disincentive to refrain from code violations.